Characteristic of strains Priestia megaterium Ср-1 and Rhodococcus jostii СА-6 demonstrating increased salt resistance - Naumovich, Nadezhda I.; Aleschenkova, Zinaida M.; Ananyeva, Irina N.; Safronava, Halina V. (Experimental Biology and Biotechnology, 2022)
The strains Priestia megaterium Ср-1 and Rhodococcus jostii CA-6 were shown to preserve phosphate-solubilising ability, nitrogen-fixing activity and synthesis of indole-3-acetic acid under osmotic stress conditions caused by sodium chloride in concentration range of 1197–2052 mmol/L, as well as to promote seed germination rate and development of small radish seedlings. Proline, betaine and sucrose were found to exert a beneficial effect on growth and ability of strains P. megaterium Ср-1 and Rh. jostii CA-6 to adapt to osmotic stress. Mass spectrometric analysis has revealed that intracellular synthesis of proline and betaine in both bacteria was directly proportional to sodium chloride concentration: rising NaCl level in the medium to 1197 mmol/L was accompanied by increase in proline level from 0.062 to 1.502 µg /mL (Rh. jostii CA-6) and from 0.089 to 2.105 µg /mL (P. megaterium Ср-1), in a similar manner betaine production grew up from 0.071 to 0.118 µg /mL (Rh. jostii СА-6) and from 0.055 to 0.219 µg /mL (P. megaterium Ср-1).
Keywords: nitrogen fixation; phosphate solubilisation; growth stimulation; osmolytes; salt-induced stress